The local community awareness on Langkawi UNESCO Global Geopark Status: Case of Kampung Padang Puteh, Langkawi, Malaysia - Ibrahim, M. S. N.; Abdul Halim, S.; Ishak, M. Y.; Hassan, S. (Ke Ai Publishing Communications, 2021)
Kampung Padang Puteh is a village that is located in southwest of Langkawi Island, Malaysia, which has been affected by tourism development since its location is exactly midway between two beach areas of Pantai Tengah and Pantai Cenang, resulting in an ever-expanding number of homestays, motels, hotels, restaurants, and food stalls. The local community is one of the important stakeholders that might be the most affected by this development and it needs to be considered in geopark development. Thus, there is a need to assess the stakeholder's current awareness that contributes to their identification with Langkawi UNESCO Global Geopark. To address this, this study aims to investigate the local community knowledge of geopark; and find out their perception about various stakeholders' roles in assisting well-being through tourism development. Data were collected through a face-to-face questionnaire with 49 household representatives by simple random sampling. The findings indicate that the local community of Kampung Padang Puteh has a moderate level of knowledge of the geopark. More than half of respondents could describe the characteristics of a geopark. However, only 18.4% of them are able to state the geopark concept correctly. They are not sure about the benefits of geopark status to their livelihood. Generally, they perceive that geopark status gives less significant impacts than duty free status on their well-being. In fact, tourists are the most important stakeholders in assisting their well-being through tourism development based on the local's perception. Thus, a good engagement between local community and authorities needs to be enhanced to lead to an increase in their sense of belonging to the area. The locals are perceived as passive in the process, and that their voices should be incorporated so that the geopark better answers to their needs and vision of empowering their role as inhabitants of geopark.